Molecular mechanism of monoamine oxidase A gene regulation under inflammation and ischemia‐like conditions: key roles of the transcription factors GATA2, Sp1 and TBP. (16th April 2015) - Gupta, Vinayak; Khan, Abrar A.; Sasi, Binu K.; Mahapatra, Nitish R.
Abstract Monoamine oxidase A (MAOA) plays important roles in the pathogenesis of several neurological and cardiovascular disorders. The mechanism of transcriptional regulation of MAOA under basal and pathological conditions, however, remains incompletely understood. Here, we report systematic identification and characterization of cis elements and transcription factors that govern the expression of MAOA gene. Extensive computational analysis of MAOA promoter, followed by 5′‐promoter deletion/reporter assays, revealed that the −71/−40 bp domain was sufficient for its basal transcription. Gel‐shift and chromatin immunoprecipitation assays provided evidence of interactions of the transcription factors GATA‐binding protein 2 (GATA2), Sp1 and TATA‐binding protein (TBP) with this proximal promoter region. Consistently, over‐expression of GATA2, Sp1 and TBP augmented MAOA promoter activity in a coordinated manner. In corroboration, siRNA‐mediated down‐regulation of GATA2/Sp1/TBP repressed the endogenous MAOA expression as well as transfected MAOA promoter activity. Tumor necrosis factor‐α and forskolin activated MAOA transcription that was reversed by Sp1 siRNA; in support, tumor necrosis factor‐α‐ and forskolin‐induced activities were enhanced by ectopic over‐expression of Sp1. On the other hand, MAOA transcription was diminished upon exposure of neuroblasts or cardiac myoblasts to ischemia‐like conditions because of reduced binding of GATA2/Sp1/TBP with MAOA promoter. In conclusion, this study revealed previously unknown roles of GATA2, Sp1 and TBP in modulating MAOA expression under basal as well as pathophysiological conditions such as inflammation and ischemia, thus providing new insights into the molecular basis of aberrant MAOA expression in neuronal/cardiovascular disease states. Dysregulation of monoamine oxidase A (MAOA) have been implicated in several behavioral and neuronal disease states. Here, we identified three crucial transcription factors (GATA2, Sp1 and TBP) that regulate MAOA gene expression in a coordinated manner. Aberrant MAOA expression under pathophysiological conditions including inflammation and ischemia is mediated by altered binding of GATA2/Sp1/TBP with MAOA proximal promoter. Thus, these findings provide new insights into pathogenesis of several common diseases. GATA2, GATA‐binding protein 2; Sp1, specificity protein 1; TBP, TATA‐binding protein.